The Effect of Social Media Advertising and eWOM on Interest in Purchasing Elzatta Products with Brand Image as a Mediating Variable - Putri, Malida Puspita Nugroho; Fikriyah, Khusnul (Jurnal Iqtisaduna, 2025)
This study aims to analyze the influence of social media advertising and eWOM on the purchase intention of Elzatta products, with brand image as a mediating variable. The method used is descriptive quantitative, with primary data collected through the distribution of online questionnaires. Sampling was conducted using a purposive sampling technique with a total of 287 respondents. Data analysis was carried out using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4 software. The results show that social media advertising does not have a direct effect on purchase intention, whereas eWOM does. Additionally, both social media advertising and eWOM influence brand image. Further findings indicate that brand image can mediate the relationship between social media advertising and eWOM with purchase intention. It is recommended that Elzatta optimize digital marketing by creating engaging advertisement content on popular social media platforms and encouraging positive eWOM.